Toner
By controlling the melting start temperature of the toner and the amount of tetrahydrofuran insoluble components in the binder resin, combined with crystalline materials, the shortcomings of the existing toner in low-temperature fixability, uneven gloss and thermal pollution are solved, and the problem of thermal damage is achieved. Higher image quality and device durability.
Patent Information
- Application Number
- CN202010592194.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-27
- Filing Date
- 2020-06-24
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-06-24
AI Technical Summary
The conventional toner is difficult to suppress gloss unevenness and end heat pollution while excellent in low temperature fixing properties, and the prior art has limited room for improvement in both aspects.
The crystalline material is combined to optimize the performance of the toner by controlling the heating rate dependence of the melting start temperature of the toner, the peak temperature of the maximum endothermic peak, and the amount of tetrahydrofuran insoluble components in the binder resin.
It achieves excellent low-temperature fixing performance while suppressing uneven gloss and end heat loss, improving image quality and equipment durability.
Smart Images

Figure CN112147860B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a toner used in a recording method using an electrophotographic method, an electrostatic recording method, or a toner jet recording method. Background Art
[0002] Electrophotographic image forming apparatuses are required to have higher performance such as higher image quality and lower energy consumption, as well as multiple functions such as the ability to print on various types of paper. In order to meet these requirements, toner performance also needs to be further improved.
[0003] First, from the viewpoint of energy saving, it is necessary to fix the toner at a lower temperature. In addition, when outputting on various sizes of paper, a toner that is resistant to end thermal offset is required. This is because when a large size paper is passed through a fixing device after a small size paper is continuously passed through the fixing device, the temperature of the non-paper passing portion of the fixing device rises due to the continuous passage of the small size paper, which promotes the generation of end thermal offset and causes image quality degradation.
[0004] There are various issues regarding high image quality, and various performance improvements of toners are required. Among them, improving image unevenness is an important issue regardless of the machine model. Image unevenness can generally be divided into density unevenness and gloss unevenness. One of the causes of gloss unevenness is that during fixing, due to the difference in the amount of deformation of the toner caused by the unevenness of the paper, the toner shape is different between the convex and concave parts on the paper and the light reflection is different.
[0005] In other words, in order to solve the problem of gloss unevenness, it is necessary to reduce the difference in the amount of toner deformation between the concave portions and the convex portions during fixing while improving the low-temperature fixability.
[0006] WO 2013 / 047296 proposes a toner having improved low-temperature fixability by adding an ester compound having a specific structure to the toner. Japanese Patent Application Publication No. 2018-173499 discloses a feature of improving the low-temperature fixability of a toner by controlling the storage elastic modulus at multiple temperatures within a specific numerical range.
[0007] Meanwhile, Japanese Patent Application Publication No. 2015-045858 proposes a toner in which hot offset at the end is improved by using a binder resin having a cross-linked structure. In addition, Japanese Patent Application Publication No. 2017-211648 proposes a toner in which the starting temperature of the storage elastic modulus of the toner and the value of the storage elastic modulus at the starting temperature are controlled within a predetermined numerical range. Summary of the invention
[0008] However, problems associated with the toner described in WO 2013 / 047296 are that gloss unevenness occurs because the viscosity after heating is low, hot offset tends to occur, and the difference in the amount of deformation of the toner between concave and convex portions is large.
[0009] Furthermore, each of the toners described in Japanese Patent Application Publication No. 2018-173499, Japanese Patent Application Publication No. 2015-045858, and Japanese Patent Application Publication No. 2017-211648 has room for further improvement in terms of suppression of gloss unevenness.
[0010] For these reasons, it is difficult to realize a toner which is excellent in low-temperature fixability and can suppress both gloss unevenness and end hot offset.
[0011] The present invention provides a toner which is excellent in low-temperature fixability and can suppress both gloss unevenness and end hot offset.
[0012] The present inventors have found that the above problems can be solved by controlling the heating rate dependency of the melting start temperature of the toner, the peak temperature of the maximum endothermic peak of the toner, and the amount of the tetrahydrofuran-insoluble component in the binder resin. This finding has led to the completion of the present invention.
[0013] That is, the toner of the present invention is:
[0014] A toner comprising toner particles, wherein the toner particles comprise a binder resin and a crystalline material, wherein:
[0015] In the dynamic viscoelasticity measurement of toner powder,
[0016] When the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 20°C / min is represented by T(A)°C and the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 5°C / min is represented by T(B)°C,
[0017] Satisfies the following formula (1):
[0018] T(A)-T(B)≤3.0℃ (1);
[0019] In differential scanning calorimetry of the toner, the peak temperature of the maximum endothermic peak is 50.0° C. to 90.0° C.; and
[0020] The amount of the tetrahydrofuran-insoluble component in the binder resin is 15% by mass to 60% by mass.
[0021] According to the present invention, a toner which is excellent in low-temperature fixability and can suppress both gloss unevenness and end hot offset can be obtained.
[0022] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the mask image used for image processing. DETAILED DESCRIPTION
[0024] In the present invention, the description of “from XX to YY” or “XX to YY” expressing a numerical range means a numerical range including a lower limit and an upper limit, and unless otherwise specified, the lower limit and the upper limit are endpoints.
[0025] The term "monomer unit" refers to a reacted form of a monomer substance in a polymer. For example, one section of carbon-carbon bonds in a main chain obtained by polymerizing a vinyl monomer in a polymer is defined as one unit.
[0026] Hereinafter, the present invention will be described in more detail with reference to embodiments, but the present invention is not limited thereto.
[0027] The toner of the present invention is:
[0028] A toner comprising toner particles, wherein the toner particles comprise a binder resin and a crystalline material, wherein:
[0029] In the dynamic viscoelasticity measurement of toner powder,
[0030] When the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 20°C / min is represented by T(A)°C and the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 5°C / min is represented by T(B)°C,
[0031] Satisfies the following formula (1):
[0032] T(A)-T(B)≤3.0℃ (1);
[0033] In differential scanning calorimetry of the toner, the peak temperature of the maximum endothermic peak is 50.0° C. to 90.0° C.; and
[0034] The amount of the tetrahydrofuran-insoluble component in the binder resin is 15% by mass to 60% by mass.
[0035] By controlling the amount of tetrahydrofuran (hereinafter also referred to as THF) insoluble components in the binder resin, hot offset and gloss unevenness can be suppressed. Here, by making the heating speed dependence of the melting start temperature of the toner equal to or less than a certain value, gloss unevenness depending on the unevenness of the paper at high-speed output, which is usually difficult to suppress, can be suppressed. In addition, the low-temperature fixability can be improved while suppressing the influence of the amount of THF insoluble components on the low-temperature fixability, and an unprecedented high level of balance among low-temperature fixability, suppression of gloss unevenness, and suppression of end hot offset can be achieved.
[0036] It is believed that the gloss unevenness is caused by the difference in the amount of deformation of the toner between the concave and convex parts of the paper, and is caused by the difference in the way of applying heat to the toner between the concave and convex parts of the paper. That is, it is believed that the amount of heat applied to the toner in the concave part is smaller than that in the convex part, and therefore, the gloss unevenness is more prominent at high-speed output.
[0037] In order to solve the above problems, the present inventors have focused on crystalline materials. By using a crystalline material having a high affinity for the binder resin, the binder resin can be plasticized.
[0038] However, the crystalline material having a high affinity for the binder resin may not plasticize the binder resin at the time of fixing. Therefore, the storage property tends to be reduced, and the binder resin is fluidized at the time of fixing, whereby the end hot offset resistance tends to be reduced. In addition, since the melted toner easily forms a smooth surface at the convex portion of the paper, the toner melted in the concave portion and the toner melted at the convex portion may have different shapes, resulting in even greater gloss unevenness.
[0039] The present inventors have found that by using a crystalline material for toner particles and controlling the peak temperature of the maximum endothermic peak of the toner and the amount of THF-insoluble components in the binder resin while suppressing the heating rate dependence of the melting start temperature of the toner, low-temperature fixability, suppression of gloss unevenness, and suppression of end hot offset can be achieved at the same time, and this finding has led to the completion of the present invention.
[0040] The toner is the following toner:
[0041] In the dynamic viscoelasticity measurement of toner powder,
[0042] When the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 20°C / min is represented by T(A)°C and the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 5°C / min is represented by T(B)°C,
[0043] Satisfies the following formula (1):
[0044] T(A)-T(B)≤3.0℃ (1).
[0045] T(A)-T(B) is preferably 2.0° C. or less, more preferably 1.5° C. or less. The lower limit of T(A)-T(B) is not particularly limited, and the smaller the better, for example, 0.0° C. or more. Numerical ranges can be combined arbitrarily.
[0046] When T(A)-T(B) exceeds 3.0°C, the heating speed dependence of the melting temperature of the toner becomes large, and when the image is output at a high speed, the toner is not heated sufficiently in the concave portion of the paper, the gloss non-uniformity further increases, and the image quality is reduced. T(A)-T(B) can be controlled by adjusting the affinity between the crystalline material and the binder resin, the amount of the crystalline material, the type and amount of the polymerizable monomer capable of forming the binder resin, and the amount and type of the crosslinking agent.
[0047] By setting the heating rate in the toner powder dynamic viscoelasticity measurement to 20°C / min, the rapid melting change of the toner during fixing can be determined. By setting the heating rate to 5°C / min, the melting change when the toner is fully heated under mild conditions can be determined.
[0048] From the viewpoint of storage stability and low-temperature fixability, T(A) is preferably 40.0° C. to 70.0° C., more preferably 45.0° C. to 65.0° C. T(A) can be controlled by using a crystalline material having a low melting point, using a crystalline material having high compatibility with the binder resin, and controlling the structure of the binder resin.
[0049] Furthermore, T(B) is preferably 37.0° C. to 67.0° C., and more preferably 42.0° C. to 62.0° C. T(B) can be controlled by changing the affinity between the crystalline material and the binder resin, the amount of the crystalline material, and the type and amount of the polymerizable monomer capable of forming the binder resin, and the like.
[0050] In differential scanning calorimetry of the toner, the peak temperature of the maximum endothermic peak is 50.0°C to 90.0°C, and the peak temperature is preferably 55.0°C to 85.0°C, and more preferably 60.0°C to 80.0°C.
[0051] When the peak temperature is lower than 50.0°C, due to the aggregation of the toner during storage or transportation, or the seepage of components located inside the toner, problems such as low density and streaks may occur at the time of image output, and image quality is reduced. When the peak temperature exceeds 90.0°C, since fluidization of the crystalline material does not occur unless the temperature exceeds 90.0°C, low-temperature fixability is reduced, further gloss unevenness occurs, and image quality is reduced.
[0052] The peak temperature can be controlled by varying the amount and type of crystalline material.
[0053] The amount of the tetrahydrofuran-insoluble component in the binder resin is 15% to 60% by mass. The amount of the THF-insoluble component is preferably 20% to 55% by mass, and more preferably 25% to 50% by mass.
[0054] When the amount of THF insoluble components is less than 15% by mass, the binder resin tends to fluidize during fixing. As a result, the hot offset resistance of the end portion is reduced. In addition, the toner melted at the convex portion of the paper as described above may be smoothed, thereby further causing gloss unevenness.
[0055] When the amount of the THF insoluble component exceeds 60% by mass, the binder resin becomes rigid and hardly deforms during fixing. As a result, low-temperature fixability may be reduced, and the toner in the concave portion of the paper is less likely to melt and deform than the toner in the convex portion, thereby further causing gloss unevenness.
[0056] The amount of the THF-insoluble component can be controlled by changing the amount and kind of the crosslinking agent in the binder resin and the kind and amount of the polymerizable monomer capable of forming the binder resin.
[0057] In a cross section of the toner observed with a transmission electron microscope, the average number of domains of the crystalline material having a major axis of 20 nm to 300 nm (hereinafter simply referred to as the average number) is preferably 50 to 500. The average number is more preferably 100 to 400.
[0058] When the average number is 50 or more, the interface between the crystalline material and the binder resin can be increased, the binder resin is easily plasticized during fixing, and the low-temperature fixability is improved or the gloss unevenness is suppressed. In addition, when the average number is 500 or less, the possibility of plasticization of the binder resin other than during fixing can be reduced, and the storage stability can be improved.
[0059] The average number can be controlled by changing the kind, amount and combination of the crystalline material, or by changing the cooling speed and cooling start temperature when the crystalline material crystallizes from a state where the crystalline material is compatible with the binder resin during toner particle production.
[0060] In the cross section of the toner observed with a transmission electron microscope, the average value of the major axis length of the domain of the crystalline material (hereinafter, also referred to as the average length) is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more. The average length is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less. These numerical ranges can be arbitrarily combined to obtain, for example, 50 nm to 300 nm.
[0061] When the average length is 20 nm or more, the crystalline material in the toner particles can maintain a crystalline state and improve low-temperature fixability. In addition, when the average length is 300 nm or less, the interface between the crystalline material and the binder resin can be increased, the binder resin is easily plasticized during fixation, the low-temperature fixability is improved, and gloss unevenness is suppressed.
[0062] The average length can be controlled by changing the kind and amount of the crystalline material, and the cooling speed and cooling start temperature when the crystalline material is crystallized from a state where the crystalline material is compatible with the binder resin during toner particle production.
[0063] In a cross section of a toner observed with a transmission electron microscope, when the number of toner particles of a crystalline material having a domain with a major diameter of 500 nm or more is represented by C and the number of toner particles of a crystalline material having no domain with a major diameter of 500 nm or more is represented by D, the following formula (2) is satisfied:
[0064] C / (C+D)≤0.20 (2).
[0065] C / (C+D) is preferably 0.15 or less, more preferably 0.10 or less. In addition, preferably, C / (C+D) is preferably 0.00 or more. By making C / (C+D) 0.20 or less, the number of domains of the crystalline material having a small interface with the binder resin is reduced, and effective fixing becomes possible, achieving excellent low-temperature fixing property and gloss unevenness suppression.
[0066] C / (C+D) can be controlled by changing the kind, amount and combination of the crystalline material, and changing the cooling rate and cooling start temperature when the crystalline material crystallizes from a state where the crystalline material is compatible with the binder resin during toner particle production.
[0067] The toner particles include a binder resin. The amount of the binder resin in the toner particles is preferably 40% by mass to 80% by mass.
[0068] The binder resin is not particularly limited, and a known resin used for toner can be used. Specific examples of the binder resin include polyester resins, polyurethane resins, and vinyl resins such as styrene acrylic resins, but are not limited thereto. The amount of the styrene acrylic resin in the binder resin is preferably 50% by mass to 97% by mass.
[0069] Examples of monomers that can be used to produce the vinyl resin are listed below.
[0070] Aliphatic vinyl hydrocarbons:
[0071] Olefins, such as ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene and other α-olefins;
[0072] Diolefins, such as butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene and 1,7-octadiene.
[0073] Cycloaliphatic vinyl hydrocarbons: monocyclic or bicyclic olefins and dienes, for example cyclohexene, cyclopentadiene, vinylcyclohexene, ethylidenebicycloheptene;
[0074] Terpenes, such as pinene, limonene, and indene.
[0075] Aromatic vinyl hydrocarbons:
[0076] Styrene and its hydrocarbon (alkyl, cycloalkyl, aralkyl and / or alkenyl) substituents, for example, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, benzylstyrene, crotylbenzene, divinylbenzene, divinyltoluene, divinylxylene and trivinylbenzene; and vinylnaphthalene.
[0077] Carboxyl-containing vinyl monomers and their metal salts:
[0078] Unsaturated monocarboxylic acids having 3 to 30 carbon atoms, unsaturated dicarboxylic acids, anhydrides thereof, and esters thereof with monoalkyl groups (1 to 27 carbon atoms).
[0079] For example, carboxyl vinyl monomers of acrylic acid, methacrylic acid, maleic acid, maleic anhydride, monoalkyl esters of maleic acid, fumaric acid, monoalkyl esters of fumaric acid, crotonic acid, itaconic acid, monoalkyl esters of itaconic acid, ethylene glycol monoether of itaconic acid, citraconic acid, monoalkyl esters of citraconic acid, and cinnamic acid.
[0080] Vinyl esters, such as vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl phthalate, diallyl adipate, isopropenyl acetate, vinyl methacrylate, methyl 4-vinylbenzoate, cyclohexyl methacrylate, benzyl methacrylate, phenyl acrylate, phenyl methacrylate, vinyl methoxyacetate, vinyl benzoate, ethyl α-ethoxyacrylate, alkyl acrylates and alkyl methacrylates having an alkyl group (linear or branched) of 1 to 22 carbon atoms (methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, methyl Propyl acrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, lauryl acrylate, lauryl methacrylate, myristyl acrylate, myristyl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, stearyl acrylate, stearyl methacrylate, eicosyl acrylate, eicosyl methacrylate, behenyl acrylate and behenyl methacrylate, etc.), dialkyl fumarate (dialkyl ester of fumaric acid, two alkyl groups are straight chain, branched chain, or alicyclic groups having 2 to 8 carbon atoms), dialkyl maleate esters (dialkyl esters of maleic acid, two alkyl groups are straight chain, branched chain or alicyclic groups having 2 to 8 carbon atoms), polyallyloxyalkanes (diallyloxyethane, triallyloxyethane, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane and tetramethylallyloxyethane), vinyl monomers having polyalkylene glycol chains (polyethylene glycol (molecular weight 300) monoacrylate, polyethylene glycol (molecular weight 300) monomethacrylate, polypropylene glycol (molecular weight 500) monoacrylate, polypropylene glycol (molecular weight 500) monomethacrylate, methanol ethylene oxide (ethylene oxide hereinafter referred to as EO) ) 10 mole adduct acrylate, methanol ethylene oxide 10 mole adduct methacrylate, lauryl alcohol EO30 mole adduct acrylate and lauryl alcohol EO30 mole methacrylate), polyacrylates and polymethacrylates (polyacrylates and polymethacrylates of polyols: ethylene glycol diacrylate, ethylene glycol dimethacrylate, propylene glycol diacrylate, propylene glycol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate and polyethylene glycol dimethacrylate).
[0081] Carboxyl-containing vinyl esters:
[0082] For example, carboxyalkyl acrylates having an alkyl chain of 3 to 20 carbon atoms, and carboxyalkyl methacrylates having an alkyl chain of 3 to 20 carbon atoms.
[0083] Among them, styrene and butyl acrylate are preferred.
[0084] The binder resin may include a non-crystalline polyester resin. Here, the non-crystalline resin is a resin in which no clear endothermic peak (melting point) is observed in differential scanning calorimetry.
[0085] Examples of monomers that can be used to produce the non-crystalline polyester resin include conventionally known divalent or trivalent or higher carboxylic acids and divalent or trivalent or higher alcohols. Specific examples of these monomers are listed below.
[0086] Examples of divalent or trivalent or higher carboxylic acids are listed below.
[0087] Dicarboxylic acids, for example oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid 1,12-dodecanedicarboxylic acid, 1,13-tridecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid and dodecenylsuccinic acid, and their anhydrides and lower alkyl esters.
[0088] Aliphatic unsaturated dicarboxylic acids, such as maleic acid, fumaric acid, itaconic acid and citraconic acid, and their lower alkyl esters and their anhydrides.
[0089] 1,2,4-Benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, their anhydrides and their lower alkyl esters.
[0090] These may be used alone or in combination of two or more.
[0091] Examples of dihydric or trihydric or higher alcohols are listed below.
[0092] Alkylene glycols (1,2-ethanediol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol and 1,20-eicosandiol);
[0093] Alkylene ether glycols (trimethylene glycol, tetramethylene glycol);
[0094] Cycloaliphatic diol (1,4-cyclohexanedimethanol);
[0095] Bisphenols (bisphenol A); and
[0096] Alkylene oxide (ethylene oxide and propylene oxide) adducts of cycloaliphatic diols, and alkylene oxide (ethylene oxide and propylene oxide) adducts of bisphenols (bisphenol A).
[0097] The alkyl chain segments of the alkylene glycol and the alkylene ether glycol may be linear or branched. Alkylene glycols having a branched structure can also be preferably used.
[0098] In addition, an aliphatic diol having a double bond may be used. Examples of the aliphatic diol having a double bond include the following compounds.
[0099] 2-Butene-1,4-diol, 3-hexene-1,6-diol and 4-octene-1,8-diol.
[0100] Furthermore, examples of the trivalent or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and the like.
[0101] These may be used alone or in combination of two or more.
[0102] In order to adjust the acid value and the hydroxyl value, monoacids such as acetic acid and benzoic acid, monoalcohols such as cyclohexanol and benzyl alcohol may be used as required.
[0103] The amount of the non-crystalline polyester resin in the binder resin is preferably 2% by mass to 8% by mass.
[0104] The glass transition temperature (hereinafter also referred to as Tg) of the binder resin measured using a differential scanning calorimeter (hereinafter also referred to as DSC) is preferably 40.0° C. to 100.0° C. from the viewpoint of low-temperature fixing property.
[0105] Toner particles include crystalline materials.
[0106] From the viewpoint of fixability, the crystalline material may include a crystalline polyester resin.
[0107] The crystalline polyester resin is, for example, a polycondensate of an aliphatic diol and an aliphatic dicarboxylic acid.
[0108] Among them, polycondensates of aliphatic diols having 2 to 12 carbon atoms and aliphatic dicarboxylic acids having 2 to 12 carbon atoms are preferred.
[0109] Examples of the aliphatic diol having 2 to 12 carbon atoms include the following compounds.
[0110] 1,2-Ethanediol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, etc. These may be used alone or in mixture of two or more.
[0111] Examples of the aliphatic dicarboxylic acid having 2 to 12 carbon atoms include the following compounds.
[0112] Oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, and lower alkyl esters and anhydrides of these aliphatic dicarboxylic acids.
[0113] Among them, sebacic acid, adipic acid and 1,10-decanedicarboxylic acid, and lower alkyl esters and anhydrides thereof are preferred. These may be used alone or in mixture of two or more.
[0114] Aromatic dicarboxylic acids can also be used. Examples of aromatic dicarboxylic acids include the following compounds.
[0115] Terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, and 4,4'-biphenyl dicarboxylic acid. Among them, terephthalic acid is preferred because it is easily available and easily forms a polymer having a low melting point.
[0116] The method for producing the crystalline polyester resin is not particularly limited, and the crystalline polyester resin can be produced by a general polyester polymerization method in which a dicarboxylic acid component and a diol component are reacted. Examples of the polymerization method include a direct polycondensation method and an ester exchange method. The polyester polymerization method can be selected and used according to the type of monomer.
[0117] The amount or addition amount of the crystalline polyester resin is preferably 1.0 to 30.0 parts by mass, and more preferably 3.0 to 25.0 parts by mass, relative to 100 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0118] The peak temperature of the maximum endothermic peak of the crystalline polyester resin measured by DSC is preferably 50.0°C to 100.0°C, more preferably 60.0°C to 90.0°C, from the viewpoint of low-temperature fixing property.
[0119] From the viewpoint of fixing performance and mold releasability, the crystalline material may include wax.
[0120] The wax is not particularly limited, and known waxes can be exemplified.
[0121] Specific examples include petroleum waxes such as paraffin wax, microcrystalline wax and mineral ester and their derivatives, montan wax and its derivatives, hydrocarbon waxes obtained by the Fischer-Tropsch process and their derivatives, polyolefin waxes represented by polyethylene and polypropylene and their derivatives, natural waxes such as carnauba wax and candelilla wax and their derivatives, and ester waxes, etc.
[0122] Here, the derivatives include oxides, block copolymers with vinyl monomers and graft-modified products.
[0123] In addition, a monoester compound containing one ester bond in one molecule, a diester compound containing two ester bonds in one molecule, and a polyfunctional ester compound containing three or more ester bonds in one molecule can be used as the ester wax. Among them, the diester compound is preferred.
[0124] Examples of the ester wax include dibehenyl sebacate, ethylene glycol dibehenate, ethylene glycol distearate, ethylene glycol arachidonate stearate, ethylene glycol stearate palmitate, butylene glycol dibehenate, butylene glycol distearate, butylene glycol arachidonate stearate, butylene glycol stearate palmitate and butylene glycol dibehenate.
[0125] The molecular weight of the ester wax is preferably 800 or less, more preferably 700 or less.
[0126] The wax preferably includes at least one compound selected from the group consisting of hydrocarbon waxes such as paraffin wax, monoester compounds, and diester compounds. The waxes may be used alone or in combination of two or more.
[0127] The amount or addition amount of the wax is preferably 1.0 to 40.0 parts by mass, and more preferably 3.0 to 35.0 parts by mass, relative to 100 parts by mass of the binder resin or the polymerizable monomer capable of forming the binder resin.
[0128] From the viewpoint of releasability and fixing performance, the peak temperature of the maximum endothermic peak of the wax measured by DSC is preferably 50.0 to 100.0° C., and more preferably 60.0 to 90.0° C. The melting point of the wax is the peak temperature of the maximum endothermic peak in differential scanning calorimetry of the ester wax.
[0129] From the viewpoint of fixing performance, the crystalline material preferably includes ester wax. Among ester waxes, diester waxes are more preferred. The binder resin can be appropriately plasticized by including the ester wax.
[0130] When the crystalline material contains ester wax, the SP value of the ester wax is calculated by SP(W)(J / cm 3 ) 1 / 2 The SP value of the binder resin is represented by SP(B)(J / cm 3 ) 1 / 2 When , the relationship of the following formula (3) is satisfied.
[0131] 2.00≤|SP(W)-SP(B)|≤4.50(3)
[0132] The SP value is also called a solubility parameter, and is a numerical value used as an indicator of solubility or affinity indicating how much a certain substance dissolves in a certain substance. Those with close SP values have high solubility and high affinity, and those with far SP values have low solubility and low affinity.
[0133] The SP value can be calculated by solubility parameter calculation software, Hansen Solubility Parameters in Practice 4th Edition 4.1.03 (available from https: / / www.hansen-solubility.com / HSPiP / ). The calculation method is based on Hansen's solubility parameter theory. In Hansen's solubility parameter theory, the evaporation energy of a molecule is divided into three types of energy: energy from dispersion force (dispersion term D), energy from dipole interaction (polarization term P), and energy from hydrogen bond (hydrogen bond term H), and they can be processed as three-dimensional vectors.
[0134] |SP(W)-SP(B)| represents the distance between the three-dimensional vector of the SP value of the ester wax and the three-dimensional vector of the SP value of the binder resin. The SP value is obtained by first calculating the dispersion term D, the polar term P, and the hydrogen bonding term H using solubility parameter calculation software, and then taking the square root of the sum of the square values of these terms to obtain the scalar of the three-dimensional vector. The three-dimensional vector of the SP value is calculated by the following method.
[0135] Homopolymer, Random Copolymer
[0136] (1): The Hansen SP value (D, P, H), molar volume and molecular weight of each unit derived from each monomer as a precursor of a vinyl resin or polyester (hereinafter also referred to as a monomer unit) were calculated using solubility parameter calculation software.
[0137] Monomer for vinyl resin: The state in which an unknown halogen X2 which does not affect the calculation result is attached to the double bond cleaved by polymerization as shown in the following formula (A) is calculated.
[0138]
[0139] Monomer for polyester: A state in which one functional group of a monomer subjected to condensation reaction becomes [—C(═O)OX] or [XC(═O)—O—] and another functional group is substituted with X as shown in the following formula (B) is calculated.
[0140]
[0141] (2): The molar volume ratio of the units derived from each monomer is calculated from the molar ratio of each monomer unit in the polymer and the molar volume of each unit.
[0142] (3): The sum of the values of the D term of the molar volume ratio multiplied by the Hansen SP value of each monomer unit is taken as the value of the D term of the Hansen SP value of the polymer. The P term and the H term are calculated similarly.
[0143] (4): Calculate the square root of the sum of the squares of the D, P, and H terms calculated in (3) and use it as the SP value of the polymer ((J / cm 3 ) 1 / 2 ).
[0144] In the method of deriving the Hansen SP value when the binder resin or the like is a mixture of two or more substances, first, the Hansen SP value (D, P, and H terms) of each substance is derived. Then, the value obtained by calculating the arithmetic mean of the parameters between the D terms, between the P terms, and between the H terms of each substance is defined as the Hansen SP value (D, P, and H terms) of the mixture.
[0145] When |SP(W)-SP(B)| is 2.00(J / cm 3 ) 1 / 2 To 4.50(J / cm 3 ) 1 / 2 In the case of , the binder resin can be appropriately plasticized, the low temperature fixability can be improved, and the storage stability can be prevented from being reduced. |SP(W)-SP(B)| is more preferably 3.00 (J / cm 3 ) 1 / 2 to 4.00(J / cm 3 ) 1 / 2 .
[0146] |SP(W)-SP(B)| can be controlled by changing the combination of the ester wax and the binder resin, the type and amount of the ester wax, and the composition of the binder resin.
[0147] The toner particles may include a colorant. Examples of the colorant include pigments, dyes, and magnetic bodies. These may be used alone or in combination of two or more.
[0148] Examples of the black pigment include carbon black such as furnace black, channel black, acetylene black, thermal black, lamp black, etc. These may be used alone or in combination of two or more.
[0149] As a colorant suitable for yellow, a pigment or a dye may be used.
[0150] Examples of yellow pigments include CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 17, 23, 62, 65, 73, 74, 81, 83, 93, 94, 95, 97, 98, 109, 110, 111, 117, 120, 127, 128, 129, 137, 138, 139, 147, 151, 154, 155, 167, 168, 173, 174, 176, 180, 181, 183, and 191, and CI Vat Yellow 1, 3, and 20. Examples of yellow dyes include CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, 162, and the like. These may be used alone or in combination of two or more.
[0151] As a colorant suitable for cyan, a pigment or a dye can be used.
[0152] Examples of cyan pigments include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 16, 17, 60, 62, 66, and the like, CI Vat Blue 6, and CI Acid Blue 45. Examples of cyan dyes include CI Solvent Blue 25, 36, 60, 70, 93, 95, and the like. These may be used alone or in combination of two or more.
[0153] A pigment or a dye may be used as a colorant suitable for magenta.
[0154] Examples of magenta pigments include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57, 57:1, 58, 60, 61, 62 3, 64, 68, 81, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238 and 254; CI Pigment Violet 19; CI Vat Red 1, 2, 10, 13, 15, 23, 29 and 35.
[0155] Examples of magenta dyes include oil-soluble dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 52, 58, 63, 81, 82, 83, 84, 100, 109, 111, 121, and 122, etc., CI Disperse Red 9, CI Solvent Violet 8, 13, 14, 21, and 27, etc., and CI Disperse Violet 1, etc.; and basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, and 40, etc., CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, and 28, etc. These may be used alone or in combination of two or more.
[0156] The amount or addition amount of the colorant (in the case other than the magnetic body) is 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, relative to 100 parts by mass of the binder resin or a polymerizable monomer capable of forming the binder resin.
[0157] The toner particles preferably include a magnetic body as a colorant. When a magnetic body is used as a colorant, a hard shell can be formed on the surface layer of the toner particles, and the durability of the toner can be improved.
[0158] Examples of magnetic bodies include magnetic iron oxides such as magnetite, hematite and ferrite, etc.; metals such as iron, cobalt and nickel, etc., or alloys of these metals with metals such as aluminum, copper, magnesium, tin, zinc, beryllium, calcium, manganese, selenium, titanium, tungsten and vanadium, etc., and mixtures thereof.
[0159] The number average particle size of the primary particles of the magnetic substance is preferably 0.50 μm or less, more preferably 0.05 μm to 0.30 μm.
[0160] The number average particle size of the primary particles of the magnetic body present in the toner particles can be measured using a transmission electron microscope.
[0161] Specifically, after the toner particles to be observed are fully dispersed in the epoxy resin, the epoxy resin is cured for 2 days at a temperature of 40° C. in the atmosphere to obtain a cured product. The obtained cured product is sliced with a microtome to obtain a thin sheet sample, an image with a magnification of 10,000 to 40,000 is taken with a transmission electron microscope (hereinafter also referred to as TEM), and the projected area of 100 primary particles of the magnetic body in the image is measured. The equivalent diameter of a circle equal to the projected area is defined as the particle size of the primary particles of the magnetic body, and the average value of 100 particles is defined as the number average particle size of the primary particles of the magnetic body.
[0162] The amount or addition amount of the magnetic body is preferably 20 parts by mass to 100 parts by mass, and more preferably 25 parts by mass to 90 parts by mass, relative to 100 parts by mass of the binder resin or a polymerizable monomer capable of forming the binder resin.
[0163] The amount of the magnetic body in the toner can be measured using a thermal analyzer TGA Q5000IR manufactured by PerkinElmer Inc. The measurement method includes heating the toner from room temperature to 900° C. at a temperature increase rate of 25° C. / min under a nitrogen atmosphere, taking the mass loss from 100° C. to 750° C. as the mass of the component after the magnetic body is removed from the toner, and taking the remaining mass as the amount of the magnetic body.
[0164] The magnetic body can be produced, for example, by the following method.
[0165] An alkali such as sodium hydroxide or the like is added to an aqueous solution of a ferrous salt in an amount equal to or greater than the iron component to prepare an aqueous solution containing ferrous hydroxide. Air is blown in while the pH of the prepared aqueous solution is maintained at 7 or higher, and an oxidation reaction of the ferrous hydroxide is performed while the aqueous solution is heated to a temperature of 70° C. or higher to first generate seed crystals serving as cores of magnetic iron oxide.
[0166] Next, based on the amount of alkali added before, the aqueous solution containing about 1 equivalent of ferrous sulfate is added to the slurry comprising seed crystals. Carry out the reaction of ferrous hydroxide, while the pH value of the mixture is maintained at 5 to 10, and air is blown in, and magnetic iron oxide grows around the seed crystals. At this time, the shape and magnetism of the magnetic body can be controlled by selecting any pH, reaction temperature and stirring conditions. Along with the oxidation reaction, the pH of the mixed solution moves to the acidic side, but preferably the pH of the mixed solution is maintained at more than 5. The magnetic body can be obtained by filtering, washing and drying the magnetic body obtained by means of a conventional method.
[0167] The magnetic body may be subjected to known surface treatment as required.
[0168] Examples of coupling agents that can be used in the surface treatment of the magnetic body include silane coupling agents and titanium coupling agents. It is more preferred to use a silane coupling agent represented by the following formula (I).
[0169] R m -Si-Y n (I)
[0170] In formula (I), R represents an alkoxy group (preferably having 1 to 3 carbon atoms), m represents an integer of 1 to 3, Y represents a functional group such as an alkyl group (preferably having 2 to 20 carbon atoms), a phenyl group, a vinyl group, an epoxy group, an acryloyl group, a methacryloyl group, etc., and n represents an integer of 1 to 3. However, m+n=4.
[0171] Examples of the silane coupling agent represented by formula (I) include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, vinyl triacetoxysilane, methyl trimethoxysilane, Oxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, trimethylmethoxysilane, n-hexyltrimethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, hydroxypropyltrimethoxysilane, n-hexadecyltrimethoxysilane and n-octadecyltrimethoxysilane, etc.
[0172] Among them, from the viewpoint of imparting high hydrophobicity to the magnetic body, it is preferable to use an alkyltrialkoxysilane coupling agent represented by the following formula (II).
[0173] C p H 2p+1 -Si-(OC q H 2q+1 )3 (II)
[0174] In formula (II), p represents an integer of 2-20, and q represents an integer of 1-3.
[0175] If p in the above formula is 2 or more, sufficient hydrophobicity can be imparted to the magnetic body. In the case where p is 20 or less, the hydrophobicity is sufficient and the aggregation between the magnetic bodies can be suppressed. In addition, in the case where q is 3 or less, the reactivity of the silane coupling agent is satisfactory and the magnetic body can be sufficiently hydrophobized.
[0176] Therefore, it is preferred to use an alkyltrialkoxysilane coupling agent in which p represents an integer of 2 to 20 (more preferably an integer of 4 to 16) and q represents an integer of 1 to 3 (more preferably 1 or 2).
[0177] When the above silane coupling agents are used, one or more of them may be used in combination for treatment. When multiple agents are used in combination, each coupling agent may be used for treatment separately or simultaneously.
[0178] The total treatment amount of the coupling agent used is preferably 0.9 to 3.0 parts by mass relative to 100 parts by mass of the magnetic body, and the amount of the treatment agent is preferably adjusted according to the surface area of the magnetic body, the reactivity of the coupling agent, and the like.
[0179] In the case where the toner particles include a magnetic body and the area ratio of the area ratio of the magnetic body within a range of 400 nm from the cross-sectional outline of the toner particles to the direction along the center of gravity of the cross section in the cross section of the toner observed with a transmission electron microscope is defined as the area ratio A1, the area ratio A1 is preferably 35.0% to 80.0%. The area ratio A1 is more preferably 40.0% to 75.0%, and further preferably 45.0% to 70.0%.
[0180] When the area ratio A1 is within the above range, at least one of storage stability and low temperature fixability is improved. The area ratio A1 can be controlled by changing the amount of the magnetic body or the medium used to make the toner particles, or by selecting the toner raw material or the surface treatment agent to change the affinity between the magnetic body and the binder resin.
[0181] The toner particles may include a charge control agent. The toner is preferably a negatively chargeable toner.
[0182] Organic metal complexes and chelates are preferred as charge control agents for negative charging. Specific examples include monoazo metal complexes; acetylacetone metal complexes; metal complexes of aromatic hydroxycarboxylic acids or aromatic dicarboxylic acids; and charge control resins described below.
[0183] Specific examples of commercially available products include Spilon Black TRH, T-77, T-95 (Hodogaya Chemical Industry Co., Ltd.), and BONTRON (registered trademark) S-34, S-44, S-54, E-84, E-88, and E-89 (Orient Chemical Industry Co., Ltd.).
[0184] The charge control agents may be used alone or in combination of two or more.
[0185] From the viewpoint of charge amount, the amount or addition amount of the charge control agent is preferably 0.1 to 10.0 parts by mass, and more preferably 0.1 to 5.0 parts by mass, relative to 100 parts by mass of the binder resin or a polymerizable monomer capable of forming the binder resin.
[0186] A polymer or copolymer having a sulfonic acid group, a sulfonate group or a sulfonate group is preferably used as the charge control resin. As the polymer having a sulfonic acid group, a sulfonate group or a sulfonate group, it is particularly preferred to include a sulfonic acid group-containing acrylamide monomer or a sulfonic acid group-containing methacrylamide monomer in a copolymerization ratio of 2% by mass or more. More preferably, the amount is 5% by mass or more in terms of copolymerization ratio.
[0187] The glass transition temperature (Tg) of the charge control resin is preferably 35°C to 90°C, the peak molecular weight (hereinafter also referred to as Mp) is 10,000 to 30,000, and the weight average molecular weight (hereinafter also referred to as Mn) is 25,000 to 50,000. When a charge control resin satisfying these characteristics is used, good friction charging characteristics can be imparted while suppressing the influence on the thermal characteristics required for the toner particles. In addition, since the charge control resin includes a sulfonic acid group, the dispersibility of the charge control resin itself in the colorant dispersion and the dispersibility of the colorant are improved, and the tinting strength, transparency and friction charging characteristics can be further improved.
[0188] The toner can also be obtained by mixing toner particles with an external additive to attach the external particles to the surfaces of the toner particles in order to improve the fluidity and / or charging performance of the toner as necessary.
[0189] For mixing the external additive, a known device such as a Mitsui Henschel mixer (manufactured by Mitsui Miike Kakoki Co., Ltd.) is preferably used.
[0190] Examples of external additives include inorganic fine particles such as silica fine particles, titanium oxide fine particles and aluminum oxide fine particles. As silica fine particles, for example, dry silica called fumed silica generated by gas phase oxidation of silicon halide and so-called wet silica made from water glass can be used.
[0191] However, it is more preferable to have fewer silanol groups on the surface and inside of the silica fine particles and to have less production residues such as Na2O and SO3 2- of dry silica.
[0192] In the case of dry silica, composite fine particles of silica and other metal oxides can also be obtained, for example, by using silicon halide together with other metal halides such as aluminum chloride and titanium chloride in a production process, and the dry silica also includes such composite fine particles.
[0193] The amount of the external additive is preferably 0.1 parts by mass to 3.0 parts by mass relative to 100 parts by mass of the toner particles.
[0194] When inorganic fine particles are used as the external additive, the amount of the inorganic fine particles can be quantified using a fluorescent X-ray analyzer based on a calibration curve prepared from a standard sample.
[0195] The number average particle diameter of primary particles of the inorganic fine particles is preferably 4 nm to 80 nm, and more preferably 6 nm to 40 nm.
[0196] When the inorganic fine particles are subjected to a hydrophobic treatment, the charging performance and environmental stability of the toner can be further improved. Examples of the treating agent used in the hydrophobic treatment include silicone varnish, various modified silicone varnishes, silicone oil, various modified silicone oils, silane compounds, silane coupling agents, other organic silicon compounds and organic titanium compounds, etc. The treating agent can be used alone or in combination of two or more.
[0197] The number average particle diameter of the primary particles of the inorganic fine particles can be calculated using a toner image magnified and photographed by a scanning electron microscope (SEM).
[0198] The method for producing the toner particles is not particularly limited, and any of dry production methods (eg, kneading and pulverization methods) and wet production methods (eg, emulsion aggregation methods, suspension polymerization methods, and solution suspension methods) may be used. Among them, the suspension polymerization method is preferably used.
[0199] In the suspension polymerization method, for example, toner particles can be produced by the following method, but the method is not limited.
[0200] The polymerizable monomer and crystalline material capable of forming a binder resin, and if necessary, a magnetic body, a polymerization initiator, a crosslinking agent, a charge control agent and other additives are uniformly dispersed to obtain a polymerizable monomer composition. Thereafter, the obtained polymerizable monomer composition is dispersed and granulated in a continuous layer (e.g., an aqueous phase) including a dispersion stabilizer using a suitable agitator, and a polymerization reaction is carried out using a polymerization initiator to obtain toner particles having a desired particle size.
[0201] The polymerization initiator used in producing the toner particles by the suspension polymerization method preferably has a half-life of 0.5 to 30 hours during the polymerization reaction. In addition, the polymerization initiator is preferably used in an addition amount of 0.5 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer capable of forming the binder resin. In this case, a polymer having a maximum molecular weight of 5,000 to 50,000 can be obtained, and the toner particles can have preferred strength and appropriate melting characteristics.
[0202] Specific examples of the polymerization initiator include azo or diazo polymerization initiators, such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile and azobisisobutyronitrile, and peroxide polymerization initiators, such as benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, di(2-ethylhexyl) peroxydicarbonate and di(sec-butyl) peroxydicarbonate, etc. Among them, tert-butyl peroxypivalate is preferred.
[0203] The aqueous medium in which the polymerizable monomer composition is to be dispersed may include a dispersion stabilizer.
[0204] As the dispersion stabilizer, known surfactants, organic dispersants and inorganic dispersants can be used. Among them, inorganic dispersants are preferred because they have dispersion stability due to their steric hindrance, and therefore, even if the reaction temperature is changed, the stability is hardly lost, washing is easy, and therefore, the toner is hardly adversely affected.
[0205] Examples of such inorganic dispersants include polyvalent metal phosphates such as tricalcium phosphate, magnesium phosphate, aluminum phosphate, zinc phosphate and hydroxyapatite; carbonates such as calcium carbonate and magnesium carbonate; inorganic salts such as calcium metasilicate, calcium sulfate and barium sulfate; inorganic compounds such as calcium hydroxide, magnesium hydroxide and aluminum hydroxide.
[0206] Relative to 100.0 parts by mass of polymerizable monomers, the usage amount of these inorganic dispersants is preferably 0.2 parts by mass to 20.0 parts by mass. In addition, dispersion stabilizers can be used alone or in combination of two or more. In addition, surfactants can be used in combination with an amount of 0.001 parts by mass to 0.1 parts by mass. When these inorganic dispersants are used, they can be used as is, but in order to obtain finer particles, inorganic dispersant particles can be generated in an aqueous medium and used.
[0207] For example, in the case of tricalcium phosphate, an aqueous solution of sodium phosphate and an aqueous solution of calcium chloride can be mixed under high-speed stirring to produce water-insoluble calcium phosphate, and a more uniform and fine dispersion can be achieved. At this time, a water-soluble sodium chloride salt is simultaneously produced as a byproduct, but it is preferred that a water-soluble salt exists in the aqueous medium because dissolution of the polymerizable monomer in water can be prevented and ultrafine toner is less likely to be produced by emulsion polymerization.
[0208] Examples of the surfactant include sodium dodecylbenzene sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, sodium stearate, potassium stearate and the like.
[0209] In the step of polymerizing the polymerizable monomer, the polymerization temperature is usually set to 40° C. or higher, preferably 50° C. to 90° C. When the polymerization is performed within this temperature range, for example, a release agent or the like to be sealed inside precipitates by phase separation, and internalization becomes more complete.
[0210] Thereafter, a cooling step of cooling from a reaction temperature of about 50° C. to 90° C. is performed to terminate the polymerization step.
[0211] After the polymerization of the polymerizable monomer is completed, the obtained polymer particles are filtered, washed and dried by a known method to obtain toner particles. The toner can be obtained by mixing an external additive with the toner particles and attaching the external additive to the surface of the toner particles. A classification step can also be introduced in the production process to shred the coarse powder and fine powder contained in the toner particles.
[0212] The toner particles may further include other additives within a range not causing substantial adverse effects.
[0213] Examples of other additives include lubricant powders such as fluorine resin powders, zinc stearate powders, and polyvinylidene fluoride powders; abrasives such as cerium oxide powders, silicon carbide powders, and strontium titanate powders;
[0214] Anti-caking agent; etc. The additive may be used after the surface thereof is subjected to a hydrophobic treatment.
[0215] The glass transition temperature (Tg) of the toner is preferably 45.0°C to 65.0°C, and more preferably 50.0°C to 65.0°C.
[0216] When the glass transition temperature is within the above range, both storage stability and low-temperature fixability can be obtained at a high level. The glass transition temperature can be controlled by the composition of the binder resin, the kind of the crystalline polyester, the molecular weight of the binder resin, and the like.
[0217] The weight average particle diameter (D4) of the toner is preferably 3.00 μm to 9.00 μm, and more preferably 5.00 μm to 8.00 μm.
[0218] By setting the weight average particle diameter (D4) of the toner within the above range, it is possible to improve the operability of the toner while sufficiently satisfying the dot reproducibility.
[0219] Furthermore, the ratio (D4 / D1) of the weight average particle diameter (D4) to the number average particle diameter (D1) of the toner is preferably less than 1.25.
[0220] The method of measuring the values of physical properties according to the present invention is described below.
[0221] Method for measuring weight average particle size (D4) and number average particle size (D1) of toner (particles)
[0222] The weight average particle diameter (D4) and number average particle diameter (D1) of the toner (particles) are calculated as follows.
[0223] As a measuring device, a precision particle size distribution measuring device "Coulter Counter Multisizer 3" (manufactured by Beckman Coulter, Inc.) based on the pore resistance method with an orifice of 100 μm was used. Dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) was used to set measurement conditions and analyze measurement data. The measurement was performed using 25,000 effective measurement channels.
[0224] As the electrolytic aqueous solution used for measurement, a solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1 mass % was used, specifically, “ISOTON II” (manufactured by Beckman Coulter, Inc.) was used.
[0225] Prior to measurement and analysis, set up the dedicated software as follows.
[0226] On the "Change Standard Measurement Method (SOM)" screen of the dedicated software, the total count in the control mode was set to 50,000 particles, the number of measurements was set to 1, and the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.) was set as the Kd value. The threshold and noise level were automatically set by pressing "Threshold / Measurement Noise Level". In addition, the current was set to 1600 μA, the gain was set to 2, the electrolytic aqueous solution was set to ISOTON II, and "Rinse the Orifice Tube" was checked "After Each Run".
[0227] In the "Pulse to Size Conversion Settings" screen of the dedicated software, set the cell spacing to logarithmic size, the size cell to 256-size cell, and the size range to 2 μm to 60 μm.
[0228] The specific measurement method is described below.
[0229] (1) Place about 200 mL of the electrolyte solution in a 250 mL glass round-bottom beaker dedicated to Multisizer 3, place the beaker in the sample holder, and stir it in a counterclockwise direction at 24 revolutions per second with a stirring rod. Use the "Rinse Orifice Tube" function of the dedicated software to remove dirt and bubbles in the orifice tube.
[0230] (2) About 30 ml of the electrolytic aqueous solution was placed in a 100-mL glass flat-bottom beaker. Then, about 0.3 mL of a dilution obtained by diluting "CONTAMINON N" (a 10% by mass aqueous solution of a neutral detergent of pH 7 for washing precision measuring instruments, the neutral detergent consisting of a nonionic surfactant, anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) by about 3 times the mass with ion-exchanged water was added thereto as a dispersant.
[0231] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) with an electrical output of 120 W in which two oscillators with an oscillation frequency of 50 kHz were built in with a phase difference of 180 degrees was prepared. A total of about 3.3 L of ion-exchanged water was put into the water tank of the ultrasonic disperser, and about 2 mL of CONTAMINON N was added to the water tank.
[0232] (4) The beaker of (2) above is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted to maximize the resonance state of the liquid surface of the electrolytic aqueous solution in the beaker.
[0233] (5) About 10 mg of the toner (particles) is added little by little to the electrolytic aqueous solution and dispersed therein in a state where the electrolytic aqueous solution in the beaker of the above (4) is irradiated with ultrasonic waves. Then, the ultrasonic dispersion treatment is further continued for 60 seconds. During the ultrasonic dispersion treatment, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.
[0234] (6) The electrolytic aqueous solution of (5) above in which the toner (particles) is dispersed is dropped into the round-bottomed beaker of (1) above which has been set in the sample holder by using a pipette, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of particles to be measured reaches 50,000.
[0235] (7) The measurement data is analyzed using the dedicated software attached to the device to calculate the weight average particle size (D4) and the number average particle size (D1). The "average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen obtained when the graph / (volume %) is set in the dedicated software is taken as the weight average particle size (D4), and the "average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen obtained when the graph / (number %) is set in the dedicated software is taken as the number average particle size (D1).
[0236] Method for measuring the peak temperature (or melting point) of the maximum endothermic peak
[0237] The peak temperature of the maximum endothermic peak of the toner or the crystalline material is measured by using a differential scanning calorimeter (DSC) Q2000 (manufactured by TA Instruments) under the following conditions.
[0238] Heating rate: 10℃ / min
[0239] Measurement start temperature: 20°C
[0240] Measurement end temperature: 180℃
[0241] The melting points of indium and zinc are used for temperature correction of the device detection unit, and the heat of fusion of indium is used for correction of the calorific value.
[0242] Specifically, 5 mg of the sample is accurately weighed and placed in an aluminum pan and measured once. An empty aluminum pan is used as a reference. The peak temperature of the maximum endothermic peak at this time is determined. For example, for wax, the peak temperature of the maximum endothermic peak is taken as the melting point.
[0243] Determination of glass transition temperature (Tg)
[0244] The glass transition temperature of the sample is determined by using an inverse heat flow curve during temperature rise obtained by differential scanning calorimetry of the peak temperature of the maximum endothermic peak, and is the temperature (°C) at the point where a straight line equidistant in the longitudinal direction from a straight line obtained by extending the baseline before and after the specific heat change and a curve of the step-like change portion of the glass transition in the inverse heat flow curve intersect each other.
[0245] Method for measuring weight average molecular weight (Mw) and peak molecular weight (Mp) of resins, etc.
[0246] The weight average molecular weight (Mw) and peak molecular weight (Mp) of a resin or the like are measured by gel permeation chromatography (GPC) in the following manner.
[0247] (1) Preparation of measurement samples
[0248] The sample and tetrahydrofuran (THF) are mixed at a concentration of 5.0 mg / mL, left to stand for 5 to 6 hours at room temperature, and then fully shaken to fully mix THF and the sample until the sample no longer agglomerates. The mixture is further left to stand for more than 12 hours at room temperature. At this time, the time from the start of mixing of the sample and THF to the end of standing is set to more than 72 hours to obtain the tetrahydrofuran (THF) soluble matter of the sample.
[0249] Thereafter, the mixture was filtered through a solvent-resistant membrane filter (pore diameter: 0.45 μm to 0.50 μm, Maishori Disk H-25-2 [manufactured by Tosoh Corporation]) to obtain a sample solution.
[0250] (2) Sample measurement
[0251] The measurement was performed under the following conditions by using the obtained sample solution.
[0252] Equipment: High-speed GPC equipment LC-GPC 150C (manufactured by Waters Corp.)
[0253] Column: 7 sets of Shodex GPC KF-801, 802, 803, 804, 805, 806 and 807 (manufactured by Showa Denko KK)
[0254] Mobile phase: THF
[0255] Flow rate: 1.0mL / min
[0256] Column temperature: 40°C
[0257] Injection volume: 100 μL
[0258] Detector: RI (refractive index) detector
[0259] When the molecular weight of a sample is measured, the molecular weight distribution of the sample is calculated from the relationship between the logarithmic value of a calibration curve prepared from several monodisperse polystyrene standard samples and the counts.
[0260] The standard polystyrene samples used for preparing the calibration curve were produced by Pressure Chemical Co. or Toyo Soda Kogyo Co., Ltd. and had a molecular weight of 6.0 × 10 2 , 2.1×10 3 4.0×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×105 , 2.0×10 6 , and 4.48×10 6 .
[0261] Cross-sectional observation of toner
[0262] Cross-sectional observation of the toner with a transmission electron microscope (TEM) is performed by staining with ruthenium. Compared with non-crystalline materials such as binder resins, the crystalline material contained in the toner is less stained with ruthenium, so that the contrast becomes clear and easy to observe. Since the amount of ruthenium atoms varies depending on the intensity of staining, the amount of ruthenium atoms in the weakly stained part is small, so the electron beam easily penetrates and becomes white on the observed image. On the other hand, the strongly stained part includes many ruthenium atoms, which are difficult for the electron beam to penetrate, and becomes black on the observed image.
[0263] First, the toner was sprayed onto a cover glass (Matsunami Glass Co., Ltd., corner cover glass, square No. 1) to form a single layer, and an Os film (5 nm) and a naphthalene film (20) were coated as a protective film by using an osmium plasma coater (filgen, Inc., OPC80T). Next, a photocurable resin D800 (JEOL, Ltd.) was loaded into a PTFE tube (inner diameter φ1.5 mm×outer diameter φ3 mm×3 mm), and the cover glass was quietly placed on the tube in an orientation such that the toner contacted the photocurable resin D800. After the resin was cured by irradiation with light in this state, the cover glass and the tube were removed to form a cylindrical resin in which the toner was embedded on the surface portion. The columnar resin was cut from the outermost surface at a distance equal to the radius of the toner (4.0 μm when the weight average particle diameter (D4) was 8.0 μm) at a cutting speed of 0.6 mm / s to open the cross section of the toner. Next, cutting was performed to obtain a film thickness of 250 nm and a thin sheet sample having a cross section of the toner was prepared. By cutting in this way, a cross section of the center portion of the toner was obtained.
[0264] The obtained thin-section sample was stained using a vacuum electron staining apparatus (filgen, Inc., VSC4R1H,) in RuO4 gas under a 500 Pa atmosphere for 15 minutes, and STEM observation was performed using TEM (JEOL, Ltd., JEM2800).
[0265] Acquire an image with a STEM probe size of 1 nm and an image size of 1,024 pixels × 1,024 pixels. In addition, adjust the "contrast" of the "detector control" panel of the image field to 1425, the "brightness" to 3750, the "contrast" of the "image control" panel to 0.0, the brightness to 0.5, and the gamma to 1.00 to obtain a TEM image.
[0266] Method for determining area ratio A1
[0267] The area ratio A1 is measured as follows.
[0268] First, a cross-sectional image of the toner is obtained by the aforementioned method using a transmission electron microscope (TEM).
[0269] Next, the obtained TEM image was binarized using the image processing software "ImageJ" (available from https: / / imagej.Nih.gov / ij / ). The toner section used for measurement is defined as follows: the circle equivalent diameter (projected area circle equivalent diameter) is obtained from the binarized image of the section, and the section whose value of the circle equivalent diameter is within the range of ±5% of the number average particle size (D1) (μm) is selected.
[0270] From the TEM image of the corresponding particles, the area other than the area required for measurement was masked using "ImageJ", and the area of the uncovered area inside the toner outline and the total area of the magnetic body present in the uncovered area were calculated. The method of obtaining the area ratio A1 using this method will be specifically described below.
[0271] First, the obtained TEM image of the cross-sectional profile of the toner (hereinafter referred to as Image 1) is binarized so that the outline and the inside of the toner are white and the other background portions are black (hereinafter referred to as Image 2).
[0272] Next, in order to calculate the magnification of the mask, the length per unit number of pixels in the image 1 is calculated. Next, from the calculated value, how many pixels fit within the range from the outline of the cross section of the toner particle to 400 nm in the centroid direction of the cross section (hereinafter referred to as x1) is calculated. Similarly, how many pixels fit in the toner particle diameter measured by using the above method (hereinafter referred to as x2) is calculated. Then, the magnification M of the mask is calculated from the following formula:
[0273] M = (x2-x1) / x2.
[0274] Next, Image 2 is reduced to the calculated magnification M (the reduced image is referred to as Image 3). In Image 3, the image is constructed so that the outline and the inside of the toner particles are black, and the other background portions are transparent.
[0275] Next, add image 2 and image 3. At this time, use "ImageCalculator" which is a function of "ImageJ" to add image 2 and image 3, and create Figure 1 In the image 4 shown, the region from the outline of the cross section of the toner particle to 400 nm in the gravity center direction of the cross section is white, and the other regions are black. The area S1 of the white region in the image 4 is measured.
[0276] Next, the created image 4 and the above-mentioned TEM image (image 1) are similarly added using the "image calculator" to create an image 5 in which the area except for the range of 400 nm from the cross-sectional contour of the toner particle toward the center of gravity of the cross section of the toner particle is masked. Image 5 is binarized, and the area S2 occupied by the magnetic body within the range is measured.
[0277] Finally, the area ratio a1 is calculated as S2 / S1.
[0278] The above operation is performed for 100 toner particles, and the arithmetic mean of the obtained 100 area ratios a1 is defined as the area ratio A1.
[0279] Method for calculating the average number of domains of crystalline material with a major axis of 20 nm to 300 nm, C / (C+D), and the average length of the domains of crystalline material
[0280] Observation is performed by the above-described method for observing a cross section of a toner, 50 toners having diameters within ±2.0 μm of the weight average particle diameter of the toner are selected, and images thereof are photographed to obtain cross-sectional images.
[0281] Crystalline materials are less stained by Ru than non-crystalline resins or magnetic bodies, and appear white to gray in cross-sectional images.
[0282] Regarding the number of domains of crystalline material, 50 toner particles are randomly selected, the number of domains having a major axis ranging from 20 nm to 300 nm is counted, and the average value among the 50 toner particles is taken as the average number of domains having a major axis ranging from 20 nm to 300 nm.
[0283] Furthermore, 50 toner particles are randomly selected, the number of toner particles having domains with a major diameter of 500 nm or more is represented by C, the number of toner particles not having domains with a major diameter of 500 nm or more is represented by D, and the value of C / (C+D) is determined.
[0284] In addition, the average length of the domain of the crystalline material is determined by randomly selecting ten colorant particles, and then further randomly selecting 100 domains of the crystalline material from the domains of the crystalline material included in the selected ten colorant particles, measuring the major diameter, and taking the average value thereof as the average length of the domain of the crystalline material in the colorant cross section.
[0285] Determination of the content of tetrahydrofuran (THF) insoluble components
[0286] 1.5 g of the toner is accurately weighed and then introduced into a cylindrical filter paper (product name: No. 86R, size 28×100 mm, Advantec Toyo Kaisha, Ltd.) which has been accurately weighed in advance, and then placed in a Soxhlet extractor.
[0287] The extraction was carried out using 200 mL of tetrahydrofuran (THF) as a solvent for 20 hours, during which the extraction was carried out at a reflux rate providing one circulation of the extraction solvent in approximately 5 minutes.
[0288] After the extraction is completed, the cylindrical filter paper is taken out and air-dried, and then vacuum-dried at 40°C for 8 hours; the mass of the cylindrical filter paper containing the extraction residue is weighed, and the mass of the cylindrical filter paper is subtracted to determine the mass of the extraction residue W1 (g).
[0289] The content W2 (g) of components other than the resin component is determined using the following procedure.
[0290] 1.5 g of toner was accurately weighed into a pre-weighed 30 mL magnetic crucible.
[0291] The magnetic crucible was placed in an electric furnace, heated at a temperature of about 900°C for about 3 hours, and then cooled in the electric furnace and in a dryer at room temperature for at least 1 hour. The mass of the crucible containing the incineration residue was weighed, and the incineration residue was calculated by subtracting the mass of the crucible, which was used as W2 (g).
[0292] The content of the THF-insoluble component in the binder resin was determined using these values and the following formula.
[0293] Content of THF-insoluble components in binder resin (mass %)
[0294] =(W1-W2) / (1.5-W2)×100
[0295] Measurement method of dynamic viscoelasticity of toner powder
[0296] The measurement was performed using a DMA 8000 (PerkinElmer Inc.) dynamic viscoelasticity measuring instrument.
[0297] Measuring tool: Material bag (P / N: N533-0322)
[0298] 80 mg of toner was clamped in a bag; it was mounted in a single cantilever; and it was installed by tightening the screws with a torque wrench.
[0299] "DMA Control Software" (PerkinElmer Inc.) dedicated software was used for the measurement. The measurement conditions were as follows.
[0300] Oven: Standard air oven
[0301] Measurement Type: Temperature Scan
[0302] DMA conditions: Single frequency / strain (G)
[0303] Frequency: 1Hz
[0304] Strain: 0.05mm
[0305] Starting temperature: 25°C
[0306] Finishing temperature: 180℃
[0307] Scanning speed: 20℃ / min or 5℃ / min
[0308] Deformation mode: Single cantilever (B)
[0309] Cross-section: Rectangular (R)
[0310] Test piece size (length): 17.5 mm
[0311] Test piece size (width): 7.5 mm
[0312] Test piece size (thickness): 1.5 mm
[0313] The starting temperature T(A)°C is calculated from the storage elastic modulus E' curve measured at a scanning rate of 20°C / min, and the starting temperature T(B)°C is calculated from the storage elastic modulus E' curve measured at a scanning rate of 5°C / min. The "starting temperature" refers to the temperature corresponding to the intersection between a straight line provided by extending the base line on the low temperature side of the E' curve to the high temperature side and a tangent line drawn at a point where the slope of the E' curve takes a maximum value.
[0314] Identification of domains in crystalline materials
[0315] Based on the TEM image of the toner particle cross section, identification of the domains of crystalline material was performed according to the following procedure.
[0316] When a crystalline material is available in the form of a raw material, its crystal structure is observed as in the above-mentioned method of observing a cross section of a ruthenium-stained toner particle using a transmission electron microscope (TEM), and the lamellar structure of the crystal in each raw material is imaged. They are compared with the lamellar structure in the domain of the cross section of the toner particle, and when the error of the lamellar interval of the lamellar is not more than 10%, the raw material forming the domain in the cross section of the toner particle can be identified.
[0317] (Separation of crystalline materials)
[0318] When a starting material of crystalline material is not available, the isolation step is performed as follows.
[0319] First, the toner is dispersed in ethanol, which is a poor solvent for the toner, and heated to a temperature exceeding the melting point of the crystalline material. At this time, pressure may be applied as needed. At this time, the crystalline material exceeding the melting point melts.
[0320] The mixture containing the crystalline material can then be recovered from the toner by solid-liquid separation.The crystalline material is isolated by fractionating the mixture into individual molecular weights.
[0321] Example
[0322] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto. Unless otherwise specified, the parts in Examples and Comparative Examples are based on mass.
[0323] Production Example of Non-Crystallinous Polyester Resin A1
[0324]
[0325] The above materials were placed in a heated and dried two-necked flask, nitrogen was introduced into the container to maintain an inert atmosphere, and the temperature was raised while stirring. Thereafter, a polycondensation reaction was performed at 150° C. to 230° C. for about 12 hours, and then the pressure was gradually reduced at 210° C. to 250° C., thereby obtaining a non-crystalline polyester resin A1.
[0326] The non-crystalline polyester resin A1 had a number average molecular weight (Mn) of 10,100, a weight average molecular weight (Mw) of 24,500, and a glass transition temperature (Tg) of 77.0°C.
[0327] Production Example of Crystalline Polyester Resin B1
[0328] - Sebacic acid 123.7 parts
[0329] -1,9-nonanediol 76.3 parts
[0330] -Dibutyltin oxide 0.1 parts
[0331] The above materials were placed in a heated and dried two-necked flask, nitrogen was introduced into the container to maintain an inert atmosphere, and the temperature was raised while stirring. Thereafter, stirring was performed at 180° C. for 6 hours. Then, while continuing to stir, the temperature was gradually raised to 230° C. under reduced pressure and further maintained for 2 hours. When the mixture became viscous, the compound was air-cooled and the reaction was stopped to obtain a crystalline polyester resin B1.
[0332] The weight average molecular weight (Mw) of the crystalline polyester resin B1 was 39,500, and the melting point was 66.0°C.
[0333] Production Example of Magnetic Iron Oxide 1
[0334] Under stirring, 55 liters of 4.0 mol / L sodium hydroxide aqueous solution were mixed with 50 liters of 2.0 mol / L Fe 2+ The ferrous sulfate aqueous solution was added to obtain a ferrous salt aqueous solution containing colloidal ferrous hydroxide. The aqueous solution was kept at 85° C. and air was blown in at 20 L / min to perform an oxidation reaction, thereby obtaining a slurry containing core particles.
[0335] The obtained slurry is filtered and washed on a filter press, and then the core particles are re-slurried by redispersion in water. To the re-slurried liquid, sodium silicate is added to provide 0.20 mass % silicon per 100 parts of the core particles; the pH of the slurry is adjusted to 6.0; magnetic iron oxide particles having a silicon-rich surface are obtained by stirring. The obtained slurry is filtered and washed with a filter press, and re-slurried with deionized water.
[0336] 500 g (10% by mass relative to the magnetic iron oxide) of ion exchange resin SK110 (Mitsubishi Chemical Corporation) was introduced into the reslurry liquid (solid content = 50 g / L) and ion exchange was performed for 2 hours under stirring. The ion exchange resin was then removed by filtration on a mesh; filtered and washed on a filter press; dried and pulverized to obtain a magnetic iron oxide with a number average particle size of 0.23 μm.
[0337] Production of silane compounds
[0338] 30 parts of isobutyltrimethoxysilane were added dropwise to 70 parts of deionized water while stirring. The aqueous solution was then kept at pH 5.5 and a temperature of 55° C. and hydrolyzed by dispersing at a peripheral speed of 0.46 m / s for 120 minutes using a dispersing impeller. The hydrolysis reaction was then terminated by making the aqueous solution pH 7.0 and cooling to 10° C. Thus, an aqueous solution containing a silane compound was obtained.
[0339] Production Example of Colorant C1
[0340] 100 parts of the above magnetic iron oxide 1 were introduced into a high-speed mixer (LFS-2 model from Fukae Powtec Corporation), and 8.0 parts of an aqueous solution containing a silane compound were added dropwise over 2 minutes while stirring at a rotation speed of 2,000 rpm. Then, it was mixed and stirred for 5 minutes. Then, in order to improve the fixation of the silane compound, drying was performed at 40°C for 1 hour, and after reducing the moisture, the mixture was dried at 110°C for 3 hours to perform a condensation reaction of the silane compound. It was then crushed and passed through a sieve with an aperture of 100 μm to obtain a colorant C1.
[0341] Crystalline materials
[0342] As the crystalline material, crystalline materials D1 to D6 shown in Table 1 were prepared.
[0343] [Table 1]
[0344]
[0345] Production Example of Toner Particles 1
[0346] Preparation of aqueous media
[0347] A total of 450 parts of a 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion exchange water, which was then heated to a temperature of 60°C, and then 67.7 parts of a 1.0 mol / L-CaCl2 aqueous solution was added to obtain an aqueous medium containing a dispersion stabilizer.
[0348] Preparation of polymerizable monomer compositions
[0349]
[0350] The above materials were uniformly dispersed and mixed using an attritor (Nippon Coke Industry Co., Ltd.).
[0351] The obtained monomer composition was heated to a temperature of 60° C., and the following materials were mixed and dissolved therein to obtain a polymerizable monomer composition.
[0352] - Crystalline material D1 5.0 parts
[0353] - Crystalline material D2 20.0 parts
[0354] - 8.0 parts of polymerization initiator (tert-butyl peroxypivalate (25% toluene solution))
[0355] The polymerizable monomer composition was loaded into an aqueous medium and granulated by stirring with TKHOMOMIXER (Tokushu Kika Kogyo Co., Ltd.) at a rotation speed of 10,000 rpm in a N2 atmosphere at a temperature of 60°C for 15 minutes.
[0356] Thereafter, the mixture was stirred with a paddle stirring blade, and polymerization reaction was performed at a reaction temperature of 70° C. for 300 minutes.
[0357] After the reaction was completed, the temperature was raised to 98°C and distillation was performed for 3 hours to obtain a reaction slurry. Thereafter, as a cooling step, water at 0°C was poured into the suspension, and the suspension was cooled from 98.0°C to 30°C at a rate of 100°C / min, then heated to 50°C and left to stand for 6 hours. The suspension was then naturally cooled to 25°C at room temperature. The cooling rate at this time was 1°C / min. Thereafter, hydrochloric acid was added to the suspension to fully wash, thereby dissolving the dispersion stabilizer, followed by filtration and drying to obtain toner particles 1. Table 2 shows the formula of the obtained toner particles 1.
[0358] Production Example of Toner 1
[0359] A total of 0.3 parts of sol-gel silica fine particles having a primary particle number average particle diameter of 115 nm were added to 100 parts of Toner Particles 1 and mixed using an FM mixer (manufactured by Nippon Coke Industries, Ltd.). Thereafter, 0.9 parts of hydrophobic silica fine particles obtained by treating silica fine particles having a primary particle number average particle diameter of 12 nm with hexamethyldisilazane and then treating with silicone oil and having a BET specific surface area value of 120 m after the treatment were further added and then mixed using an FM mixer (manufactured by Nippon Coke Industries, Ltd.) to obtain Toner 1. 2 / g. The properties of the obtained Toner 1 are shown in Table 3 below.
[0360] Example 1
[0361] LaserJet Pro M12 (manufactured by Hewlett-Packard Company) of a one-component contact developing system was used as an image forming apparatus after being modified to 300 mm / sec, which is faster than the original process speed, so that the fixing temperature can be changed.
[0362] The evaluation results are shown in Table 4. The evaluation method and evaluation criteria in each evaluation are as follows.
[0363] Evaluation 1: Evaluation of uneven gloss
[0364] The gloss unevenness was evaluated in a normal temperature and humidity environment (temperature: 25.0°C, relative humidity: 60%), and OCE RED LABEL (basis weight: 80 g / m 2 ) as paper.
[0365] The gloss was measured using a handheld gloss meter PG-1 (manufactured by Nippon Denshoku Industries Co., Ltd.). In the measurement, the light projection angle and the light receiving angle were set to 75°, respectively. Regarding the image gloss value, the gloss values (glossiness) of ten points randomly selected from the output image were measured, and the gloss unevenness was evaluated by the difference between the highest glossiness and the lowest glossiness. The evaluation criteria are as follows.
[0366] A: The gloss difference is less than 2.00%.
[0367] B: The gloss difference is 2.00% or more and less than 5.00%.
[0368] C: The gloss difference is 5.00% or more and less than 10.00%.
[0369] D: The glossiness difference is 10.00% or more.
[0370] Evaluation 2: Evaluation of heat fouling resistance of the end portion
[0371] The heat-smear resistance of the edge was evaluated in a normal temperature and humidity environment (temperature: 25.0°C, relative humidity: 60%), using a basis weight of 66 g / m 2 After printing 500 horizontal line patterns with a printing percentage of 2% on A5 size paper, 100 horizontal line patterns with a printing percentage of 2% were continuously printed on A4 size paper. The number of prints with end stains occurring at the ends of the A4 size paper was visually observed and evaluated according to the following criteria. The disappearance of end stains on a small number of prints indicates excellent end stain resistance.
[0372] A: No end stain occurred.
[0373] B: The end stain disappears on the fifth sheet.
[0374] C: The end stain disappears on the tenth sheet.
[0375] D: Even after the tenth sheet, the edge stain does not disappear.
[0376] Evaluation 3: Evaluation of low temperature fixability
[0377] The low-temperature fixability was evaluated under a normal temperature and humidity environment (temperature: 25.0° C., relative humidity: 60%).
[0378] A modification was made so that the fixing temperature of the fixing unit in the image forming apparatus can be arbitrarily set. Using this apparatus, the fixing temperature of the fixing unit was adjusted in the range of 180°C to 230°C at intervals of 5°C, and FOX RIVER BOND paper (110 g / m 2 ), and a solid black image was output at a print percentage of 100%. At this time, whether or not there were blank spots in the image of the solid image portion was visually evaluated, and the low-temperature fixability was evaluated by the minimum temperature at which the blank spots were generated.
[0379] A: Blank spots appear below 200°C.
[0380] B: A blank spot appears at 200°C or higher and lower than 210°C.
[0381] C: A blank spot appears at 210°C or higher and lower than 220°C.
[0382] D: Blank spots appear above 220°C.
[0383] Evaluation 4: Evaluation of storage stability
[0384] In the storage stability test, a solid image was obtained under a normal temperature and humidity environment (temperature: 25.0°C, relative humidity: 60%), and then stored for 40 days under a severe environment (temperature: 40.0°C, relative humidity: 95%) together with a developing device. After storage, a solid image was output under a normal temperature and humidity environment (temperature: 25.0°C, relative humidity: 60%), and a comparative evaluation of the image density before and after storage was performed. The density of the solid image was measured with a Macbeth reflection densitometer (manufactured by Macbeth).
[0385] A: The concentration difference is less than 0.05.
[0386] B: The density difference is 0.05 or more and less than 0.10.
[0387] C: The density difference is 0.10 or more and less than 0.20.
[0388] D: The concentration difference is 0.20 or more.
[0389] Production Examples of Toner Particles 2 to 17, 19 to 21, and 23 to 27
[0390] Toner particles 2 to 17, 19 to 21, and 23 to 27 were obtained in the same manner as in the production example of toner particle 1, except that the conditions were changed as shown in Table 2.
[0391] [Table 2]
[0392]
[0393] [Table 3]
[0394]
[0395] [Table 4]
[0396]
[0397] Production Example of Toner Particles 18
[0398] Preparation of aqueous media
[0399] After 585 parts of a 0.1 mol / L-Na3PO4 aqueous solution were added to 720 parts of ion exchange water and the temperature was raised to 60°C, 88.0 parts of a 1.0 mol / L-CaCl2 aqueous solution were added to obtain an aqueous medium containing a dispersion stabilizer.
[0400] Preparation of non-crystalline polyester resin solution
[0401]
[0402] The above materials were uniformly dispersed and mixed using an attritor (Nippon Coke Industry Co., Ltd.) to prepare a non-crystalline polyester resin solution.
[0403] Preparation of pigment dispersion
[0404] - 40.0 parts of styrene
[0405] - Colorant C2 (copper phthalocyanine pigment (pigment blue 15:3)) 10.0 parts
[0406] - Negative charge control agent T-77 (manufactured by Hodogaya Chemical Industry) 1.0 part
[0407] The above materials were mixed, and the mixture was stirred with zirconium oxide beads (3 / 16 inch) using an attritor (Nippon Coke Industry Co., Ltd.) at 200 rpm for 4 hours, and then the beads were separated to prepare a pigment dispersion.
[0408] Preparation of polymerizable monomer compositions
[0409] The monomer composition obtained by mixing the non-crystalline polyester resin solution and the pigment dispersion liquid was heated to a temperature of 60° C., and the following materials were mixed and dissolved therein to form a polymerizable monomer composition.
[0410] - Crystalline material D1 5.0 parts
[0411] - Crystalline material D2 20.0 parts
[0412] - 8.0 parts of polymerization initiator
[0413] (tert-Butyl peroxypivalate (25% toluene solution))
[0414] The polymerizable monomer composition was loaded into an aqueous medium and stirred with a TK Homomixer (Tokushu Kika Kogyo Co., Ltd.) at a rotation speed of 10,000 rpm at a temperature of 60° C. and a nitrogen atmosphere for 15 minutes, and granulated.
[0415] Thereafter, stirring was performed with a paddle stirring blade, and polymerization reaction was performed at a reaction temperature of 70° C. for 300 minutes.
[0416] After the reaction was completed, the temperature was raised to 98°C, and distillation was performed for 3 hours to obtain a reaction slurry. Thereafter, as a cooling step, water at 0°C was poured into the suspension, and the suspension was cooled from 98.0°C to 30°C at a rate of 100°C / min, and then heated to 50°C and maintained for 6 hours. Then, the suspension was naturally cooled to 25°C at room temperature. The cooling rate at this time was 1°C / min. Thereafter, hydrochloric acid was added to the suspension, and sufficient washing was performed to dissolve the dispersion stabilizer, and then filtered and dried to obtain the toner particles 18. Table 2 shows the formula of the obtained toner particles 18.
[0417] Production Example of Toner Particles 22
[0418] Toner particles 22 were obtained in the same manner as in the Production Example of Toner Particles 18 except that the conditions were changed as shown in Table 2.
[0419] Toner Production Examples 2 to 27
[0420] Toners 2 to 27 were obtained in the same manner as in the Production Example of Toner 1, except that Toner Particles 2 to 27 were used respectively in place of Toner Particle 1. Table 3 shows the physical properties of Toners 2 to 27 obtained.
[0421] Furthermore, Toners 2 to 27 were evaluated in the same manner as in Example 1. Table 4 shows the results.
[0422] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles, wherein the toner particles comprise a binder resin, a crystalline material and a magnetic body, wherein the toner is characterized in that: The amount of the magnetic substance is 25 to 85 parts by mass relative to 100 parts by mass of the polymerizable monomer capable of forming the binder resin, In the dynamic viscoelasticity measurement of toner powder, When the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 20°C / min is represented by T(A)°C and the starting temperature of the storage elastic modulus E' obtained when the temperature is increased by 5°C / min is represented by T(B)°C, Satisfies the following formula (1): T(A) - T(B) ≤3.0℃ (1); In differential scanning calorimetry of the toner, the peak temperature of the maximum endothermic peak is 50.0° C. to 90.0° C.; In a cross section of the toner observed with a transmission electron microscope, when the area ratio of the magnetic body in a range from the outline of the cross section of the toner particle to 400 nm in the direction of the center of gravity of the cross section is represented by an area ratio A1, The area ratio A1 is 35.0% to 80.0%, and The amount of the tetrahydrofuran-insoluble component in the binder resin is 15% by mass to 60% by mass. 2 . The toner according to claim 1 , wherein in a cross section of the toner observed with a transmission electron microscope, an average number of domains of the crystalline material having a major axis of 20 nm to 300 nm is 50 to 500.
3. The toner according to claim 1 or 2, wherein in a cross section of the toner observed with a transmission electron microscope, when the number of toner particles having domains of crystalline material having a major diameter of 500 nm or more is represented by C and the number of toner particles not having domains of crystalline material having a major diameter of 500 nm or more is represented by D, the following formula (2) is satisfied: C / (C + D) ≤ 0.20 (2). 4 . The toner according to claim 1 , wherein in a cross section of the toner observed with a transmission electron microscope, an average value of the major axis length of the domains of the crystalline material is 50 nm to 300 nm. 5 . The toner according to claim 1 , wherein the crystalline material comprises an ester wax. The toner according to claim 5 , wherein the molecular weight of the ester wax is 800 or less.
